PELAKSANAAN PEMILIHAN KEPALA DESA KARTIASA KECAMATAN SAMBAS TAHUN 2019 PERSPEKTIF SIYASAH SYAR’IYAH - Hasiah Hasiah; Sri Sudono Saliro; Yudi Purwadi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
The Village Head Election in Sambas Regency was formed based on considerations of effectiveness, efficiency, and rationale in accordance with regional needs and capabilities as well as coordination, integration, synchronization and simplification as well as institutional communication between regional centers so that an election of a village head was carried out that truly reflected the will of the community village in determining the best leader. Based on the results of the research, the implementation of the Kartiasa Village Head Election refers to the legal basis for the Sambas Regency Regional Regulation Number 6 of 2015 concerning Village Head Election, and the Sambas Regent Regulation Number 27 of 2015 concerning Village Head Elections. The stages are: preparation, voter registration and nomination, voting, and determination / endorsement. Whereas the process and mechanism for the Village Head Election in Kartiasa Village, starting from the preparation stage whose activities include the formation of the Pilkades committee, up to the stipulation / ratification stage, in which the election results are submitted by the Election Committee to the BPD and from the BPD to the Regent through the District Head, in accordance with siyasah syar'iyyah (Islamic political system